Hollow carbon-shell/carbon-nanorod arrays for high performance Li-ion batteries and supercapacitors1. Issue 11 (7th February 2015) - Wang, Shengbin; Xing, Yalan; Xiao, Changlei; Wei, Xin; Xu, Huaizhe; Zhang, Shichao
<x xml:space="preserve">Abstract</x> A novel N-doped hollow hierarchical carbon-shell/carbon-nanorod arrays (N-HPC) have been constructed. When evaluated as electrode material for LIBs and supercapacitors, the N-HPC manifests outstanding rate capability and excellent cycling performance.